The Gifted Rating Scales - School Form in Greek elementary and middle school learners: a closer insight into their psychometric characteristics - Sofologi, Maria; Papantoniou, Georgia; Avgita, Theodora; Dougali, Anna; Foti, Theodora; Geitona, Aikaterini-Rafaela; Lyraki, Aikaterina; Tzalla, Anastasia; Staikopoulou, Maria; Zaragas, Harilaos; Ntritsos, Georgios; Varsamis, Panagiotis; et al. (Frontiers in Psychology, 2023)
The Gifted Rating Scales - School Form (GRS-S), an evaluation tool for the identification of gifted elementary and middle school children, was the subject of the current study, which focused on its psychometric features (internal consistency reliability and structural validity). Four hundred and eighty-nine teachers (342 women, 139 men, and 8 without gender declaration) used the GRS-S to estimate the dimensions of giftedness in their students for the current study. Particularly, 489 children (253 girls and 236 boys) were evaluated by their teachers. Eight elementary and middle school classes and sixteen 6-month age bands were used to stratify the student population. The scales’ outstanding internal consistency and good factorial validity were revealed by statistical analyses (EFA, CFA, and Cronbach’s coefficients). According to the current research findings, the GRS-S as a reliable and valid assessment tool for identifying gifted students (by their teachers) within the Greek cultural environment.